2020
DOI: 10.1002/ccr3.2863
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary hyperplasia secondary to primary hypothyroidism

Abstract: Severe primary hypothyroidism should be considered in the differential diagnosis of pituitary enlargement. Thyroid hormone replacement therapy should lead to regression of pituitary hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The literature search yielded 649 potentially relevant articles, spanning from January 1996 to December 2023. Following the removal of duplicates and the review of titles, abstracts, and full-length articles, we identified 55 articles [ 6 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 649 potentially relevant articles, spanning from January 1996 to December 2023. Following the removal of duplicates and the review of titles, abstracts, and full-length articles, we identified 55 articles [ 6 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, to re ect the pituitary gland's vast regulatory role in the body, we initially sought to investigate relationships between pituitary [68Ga]-DOTATATE uptake and clinical variables such as FSH, menopause, TSH, oral contraception (OCP) use, BMI, and other forms of exogenous hormones, where were not included in the nal analysis due to di culties accessing the data, inconsistent documentation, and general scarcity of such information in the electronic medical record. Pituitary gland volume may change with oral contraceptive use, pregnancy, nulliparity, hormone replacement therapy, obesity, and primary hypothyroidism [35][36][37][38][39][40][41]. Future studies in relation to the aforementioned variables will further enhance our understanding of [68Ga]-DOTATATE PET in various clinical settings.…”
Section: Discussionmentioning
confidence: 99%